Chalo Jahaji : on a journey through indenture in Fiji - Lal, Brij V. (Canberra, ACT : ANU E Press, 2012)
"Indians of the indentured diaspora have a remarkable lot in common. Meeting as 'foreign' students in India, the girmitiya descendants from Guyana, Mauritius, Fiji and Natal immediately develop a close bonding because of their use of common words, similarity of names, culinary preferences and transported texts. In similar manner, when Brij Lal visited Trinidad in 1998, both his physical as well as his spiritual being enabled him to blend immediately with his Bhojpuri brethren in Chinidad Tapu. His book, Chalo Jahaji, focusses ostensibly on the girmit experience in Fiji. It seeks to tell the story of 60,000 Indians who were indentured there between 1879 and 1916."
"First published by Division of Pacific and Asian History, RSPAS, ANU, 2000"
Title from title screen (viewed on 21 December 2012)
Includes bibliographical references and index.
Mode of access: Available online. Address as at 12/04/13
Selected for archiving
Keywords: Lal, Brij V; Indentured servants -- Fiji -- Biography; Fiji -- History; Australian